EFFECT OF SOWING DATES , PLANTING DISTANCES AND CULTIVARS ON SEED YIELD IN SUMMER SQUASH ( Cucurbita pepo L.) - Mohammad Talal Al-Habar (Mesopotamia Journal of Agriculture)
A field experiment was conducted during spring season of 2007 and 2008 , to study the seed yield as affect by three sowing dates (10th Feb , 20th Feb and 1st Mar.), with two planting distances ( 25 and 35 cm) , was carried out in the first season on two cultivars namely Nadi F1 and Asma F1 of summer squash , whereas, the second season included three cultivars were included in the second season by introducing Mulla-Ahmad cultivar (inbred) . The results indicated that plants sowed in the first and second dates gave the highest values in dry weight plant -1 , total fruit yield and seed yield plant -1 , while , plant distance at 25 cm produced greatest total seeds yield . The hybrid Asma was distinguished with most studied traits as compared with Nadi F1 and Mulla-Ahmad cultivars . The best interaction in the first season was obtained from plants sowed in the first planting date at 25 cm of Nadi cultivar , whereas in the second season Asma cultivar gave the highest seeds yield in the same previously mentioned interaction treatment .